A comparative study on PAH characteristics of ethanol and ammonia as fuel additives in a premixed flame. (April 2022) - Li, Youping; Zhang, Yiran; Yang, Guofeng; Fuentes, Andrés; Han, Dong; Huang, Zhen; Lin, He
Abstract: Due to issues towards polycyclic aromatic hydrocarbons (PAH) emissions and energy security, the renewable and non- or low-sooting tendency fuels are growing increased attention as alternatives to conventional fossil fuels. One feasible approach is to co-fire ethanol and ammonia with hydrocarbons, thus improving their combustion properties and pollutant emissions. This study presents a comparative study about the influence of ethanol and ammonia addition on PAH formation with the same blending ratios up to 30% by mole fraction in premixed C2 H4 flames. The axial fluorescence intensities in three wavelength bands were measured to represent concentrations of 2- and 3-ring, 4-ring, 5-membered-ring aromatic species using the laser-induced fluorescence (LIF) technique. Experimental results indicated that both ethanol and ammonia addition could cause PAH reductions in premixed ethylene flames as their blending ratios increase. Further, ammonia was found more efficient than ethanol at inhibiting PAH formation under the same blending ratio. A chemical kinetic analysis was conducted to reveal the inhibiting role of ethanol and ammonia as substituents to ethylene on PAH formation. It was found that both ethanol and ammonia addition chemically suppress benzene formation and subsequent PAH growth due to the low yield of C2 H2 and C3 H3 . Meantime, the additional C1 and C2 supply from ethanol decomposition could explain the relatively lower inhibiting effects on C6 H6 and PAH formation as compared to the NH3 doped flames. Highlights: Doping ethanol and ammonia reduced PAHs in premixed ethylene flames. NH3 and ethanol suppressed benzene formation through C2 H2 →C3 H3 →C6 H6 . The additional carbon species from ethanol explained lower inhibiting effects on PAHs. The decreased C2 H2 concentration suppressed PAH formation by HACA reactions.